The use of technological measures in improving the body growth and morphofunctional properties of the udder of cows (Journal of Pharmaceutical Negative Results, 2022)
The article presents information on the positive impact of the use of the "Imnamak" food additive in the cultivation of Holstein females in the "Karpat-ola Chashmasi" farm in the Yakkabog district of the Kashkadarya region, as well as the positive effect of active massage of the udder of heifers during the period of 7-8 months of pregnancy on their growth, development and morphofunctional characteristics of the udder of first-calf heifers.